Comparison of Low-Cost Methods for Soil Water Holding Capacity. Issue 2 (19th January 2023) - Govindasamy, Prabhu; Mahawer, Sonu Kumar; Mowrer, Jake; Bagavathiannan, Muthukumar; Prasad, Mahendra; Ramakrishnan, Srinivasan; Halli, Hanamant M; Kumar, Sunil; Chandra, Amresh
ABSTRACT: The use of cost-effective methods for measurement of WHC is common in underdeveloped and developing countries, but the accuracy of these cost-effective methods compared to the sophisticated and more expensive alternatives is unclear. To compare different WHC measurement methods, 30 random samples of clay loam and sandy clay loam soils of Jhansi, India were used. The methods compared here were: FAO in-situ method (FAO), Keen-Raczkowski box method (KM), funnel method (FM), column method (CM) and pressure plate method (PPA). For WHC measurements the PPA results were comparable to KM and FM methods for sandy clay loam, and KM and FAO methods for clay loam. Therefore, until a reliable method that matches the results of sophisticated analytical methods of soil water measurement is available, different inexpensive analytical methods can be used, but they must be chosen with caution. The findings from this study will facilitate appropriate selection of a suitable method.